Predicting Offender-Generated Echange Rates: Implications for a Theory of Sentence Severity - Wood, Peter B.; Mooney, Jennifer L.; Minor, Kevin I.; May, David C. (Crime & delinquency, 2005)
We solicited offender-generated exchange rates between prison and several noncustodial sanctions from a sample of 588 offender current/v serving community based punishments. We then regressed these exchange rates on demographic, attitudinal, and correctional experience indicators. Males, Blacks, older offenders, offenders with prison experience, and those who agree most strongly with reasons to avoid alternative sanctions are likely to serve less of a given alternative to avoid imprisonment. In addition, offender- generated exchange rates are used to develop a ranking of sanction severity that includes prison and nine intermediate sanctions. Implications of these findings for correctional policy, practice. and a theory of sentence severity are discussed. [ABSTRACT FROM AUTHOR]